Pengaruh Service Quality dan Staff Behaviour terhadap Brand Loyalty TIKI di Jakarta Utara: Customer Satisfaction sebagai Variabel Mediasi - Rendy Surya (Universitas Tarumanagara, 2022)
The purposes of this study are: First, to explore the effect among service quality on brand loyalty. Second, to explore the effect among staff behaviour on brand loyalty. Third, to explore the effect among service quality on customer satisfaction. Fourth, to explore the effect of customer satisfaction on brand loyalty. Fifth, to find out if customer satisfaction is able to mediate service quality toward brand loyalty. The populations of this research are all TIKI’s customer in Jakarta. The samples of this research are collected from TIKI’s customer in North Jakarta. The method of data collection was conducted by distributing questionnaires 200 respondents. The technique of data analysis used in this study was Partial Least Square and indirect effect test for mediation variable to example the hypotheses. The result are: first, the relationship between service quality have a significant and positive effect toward brand loyalty; second, the relationship between staff behaviour have a significant and positive effect toward brand loyalty; third, the relationship between service quality have a significant and positive effect toward customer satisfaction; forth, customer satisfaction have a significant and positive effect toward brand loyalty; fifth, customer satisfaction will mediate the effect between service quality on brand loyalty.